Neutron Radiation Tests about FeCr Slag and Natural Zeolite Loaded Brick Samples - Vedat Veli Cay; Mucahit Sutcu; Osman Gencel; Turgay Korkut (Science and Technology of Nuclear Installations)
Neutron shielding performances of new brick samples are investigated. Brick samples including 10, 20, and 30 percentages of ferrochromium slag (FeCr waste) and natural zeolite are prepared and mechanical properties are obtained. Total macroscopic cross sections are calculated by using results of 4.5 MeV neutron transmission experiments. As a result, neutron shielding capacity of brick samples increases with increasing FeCr slag and natural zeolite percentages. This information could be useful in the area of neutron shielding.